2001
DOI: 10.1348/000709901158389
|View full text |Cite
|
Sign up to set email alerts
|

Inattention, hyperactivity and impulsiveness: Their impact on academic achievement and progress

Abstract: The achievement of children with high scores on the behaviour rating scale replicated previous studies which investigated the achievement of children with ADHD. The behaviour rating scale could be a useful tool for raising the awareness of teachers to young children with severe behavioural problems of inattention, hyperactivity and impulsivity who have not been diagnosed as having ADHD but may nevertheless be at risk of similar outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
142
0
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(167 citation statements)
references
References 10 publications
15
142
0
10
Order By: Relevance
“…Being rated as severely inattentive at a young age does not determine a child's progress; it simply suggests that academic progress is likely to be less than his or her peers with no behavioural difficulties. For example, there will have been some variation in the reliability of teachers' ratings as suggested by Merrell and Tymms (2001) and more consistent ratings might reduce the apparent variation in progress. On the other hand, a child's behaviour in the first year of school is likely to change; some children will have taken longer than others to settle into the school environment and may have displayed behavioural symptoms for that reason.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Being rated as severely inattentive at a young age does not determine a child's progress; it simply suggests that academic progress is likely to be less than his or her peers with no behavioural difficulties. For example, there will have been some variation in the reliability of teachers' ratings as suggested by Merrell and Tymms (2001) and more consistent ratings might reduce the apparent variation in progress. On the other hand, a child's behaviour in the first year of school is likely to change; some children will have taken longer than others to settle into the school environment and may have displayed behavioural symptoms for that reason.…”
Section: Discussionmentioning
confidence: 99%
“…Teachers rated each pupil's behaviour on a yes/no scale for each criterion and were asked to consider a criterion met only if the behaviour has persisted for at least six months and is considerably more frequent than that of most other children of the same gender and developmental level. Information about the reliability and validity of this scale can be found in Merrell and Tymms (2001).…”
Section: Behaviour At the End Of The First School Yearmentioning
confidence: 99%
“…Indeed, reading difficulties and CD were shown to be unrelated except by their common correlation with the attention deficits reported in ADHD (Rapport, Scanlan & Denney, 1999;Carroll, Maughan, Goodman & Meltzer, 2004). Furthermore, despite the well-documented association between ADHD and reading problems (Merrell & Tymms, 2001;Hinshaw, 1992), a growing literature has documented that it is the inattentive subtype of ADHD, when compared with the hyperactive subtype, which correlates more strongly with the reading difficulties of school-aged children (Willcutt & Pennington, 2000a;McGee, Prior, Williams, Smart & Sanson, 2002). Importantly, longitudinal studies have presented evidence that inattentive behavior during kindergarten predicted reading achievement by the end of elementary school (Duncan et al, 2007;Rabiner & Coie, 2000), and that inattention reported at elementary school significantly predicted long-term educational attainment at age 22-23 (Pingault et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…The potential adverse consequences of ADHD include the development of additional disorders, educational problems including academic underachievement, difficulties with social relationships, employment problems, and criminal activity [2][3][4][5][6]. It is therefore important that children with, or at risk of, ADHD are appropriately identified and they and their caregivers are able to access appropriate interventions and support.…”
Section: Introductionmentioning
confidence: 99%